Low-load compression testing: a novel way of measuring biofilm thickness - Paramonova, Ekaterina; de Jong, Ed D; Krom, Bastiaan P; van der Mei, Henny C; Busscher, Henk J; Sharma, Prashant K (Applied and environmental microbiology, 2007)
Biofilms are complex and dynamic communities of microorganisms that are studied in many fields due to their abundance and economic impact. Biofilm thickness is an important parameter in biofilm characterization. Current methods of measuring biofilm thicknesses have several limitations, including application, availability, and costs. Here, we present low-load compression testing (LLCT) as a new method for measuring biofilm thickness. With LLCT, biofilm thicknesses are measured during compression by inducing small loads, up to 5 Pa, corresponding to 0.1% deformation, making LLCT essentially a nondestructive technique. Comparison of the thicknesses of various bacterial and yeasts biofilms obtained by LLCT and by using confocal laser scanning microscopy (CLSM) resulted in the conclusion that CLSM underestimates the biofilm thickness due to poor penetration of different fluorescent dyes, especially through the thicker biofilms, whereas LLCT does not suffer from this thickness limitation.